Zinc-barium-gallium sulfide green luminescent material activated by divalent europium as well as preparation method and application of zinc-barium-gallium sulfide green luminescent material

By developing divalent europium-activated zinc barium gallium sulfide green luminescent material, the existing narrowband green phosphors are solved, and the problems of low efficiency and poor thermal stability in LED backlight applications are achieved, achieving efficient and stable green light emission and wide color gamut display effects.

CN119899660APending Publication Date: 2025-04-29UNIV OF SCI & TECH BEIJING
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411971088.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing narrowband green phosphors have problems such as low efficiency, poor thermal stability, large particle size and excessive emission spectrum in LED backlight applications, which limit the color gamut and resolution of LCD display devices.

Method used

A divalent europium-activated zinc barium gallium sulfide green luminescent material is developed, with the general chemical formula of ZnBa2Ga6S12:Eu2+. Materials with excellent luminescent properties are prepared by Eu2+ doping ions entering the crystal lattice, combined with high-temperature solid phase reaction and hydrogen sulfide atmosphere.

Benefits of technology

The material exhibits high luminescence internal/outer quantum efficiency under ultraviolet/violet light excitation. The half-height width of the emission spectrum is narrow, the color gamut is wide, and has good luminescence thermal stability and small and uniform grains. It is suitable for wide color gamut LCD display devices and high color development quality full spectrum LED devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899660A_ABST
    Figure CN119899660A_ABST
Patent Text Reader

Abstract

The invention provides a zinc-barium-gallium sulfide green luminescent material activated by divalent europium and a preparation method and application thereof, and relates to the technical field of luminescent material preparation. The general chemical formula of the zinc-barium-gallium sulfide green luminescent material is ZnBa2Ga6S12: Eu < 2 + >. Wherein Eu < 2 + > enters crystal lattices as doping ions. The excitation spectrum of the material can cover a wide range of 280-480 nm, so that ultraviolet light / purple light / blue light can efficiently excite the material. The main peak range of the emission wavelength generated by the zinc-barium-gallium sulfide green luminescent material is 505-530 nm. When the material is excited by ultraviolet / purple light (340-420 nm), the optimal luminescence internal / external quantum efficiency of a sample is not lower than 75% / 55%, and when the material is excited by blue light (420-460 nm), the optimal luminescence internal / external quantum efficiency of the sample is not lower than 55% / 35%. The ultra-high-resolution liquid crystal display wide-color-gamut LED backlight source and the ultra-high-color-rendering white-light LED lighting device can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of luminescent material preparation, and in particular to a divalent europium-activated zinc barium gallium sulfide green luminescent material and a preparation method and application thereof. Background Art

[0002] As the flat panel display technology with the highest market share and the most mature technology, the liquid crystal display (LCD) screen has become the most widely used display device with its advantages of low power consumption, low cost, long life and high-definition display quality. However, liquid crystal is not the source of its light. The light of the LCD screen comes from its white light LED background light source. As an important component, the quality of the LED backlight determines the performance indicators of the LCD display screen, such as color saturation, color resolution and display quality. Among them, the color gamut is an important parameter for evaluating the quality of LCD backlight sources, usually expressed in NTSC (%). It is specifically manifested as the size of the area enclosed by the RGB three primary color coordinates of the white light LED in the CIE-xy chromaticity diagram. The wider the color gamut of the LED backlight source, the larger the color display range of the resulting display device, and the more realistic and vivid the resulting image.

[0003] At present, the display LED backlight source is mainly realized by phosphor conversion white light LED (pc-WLED). In the early scheme, the display LED was realized by a combination of ordinary LED lighting devices, that is, the blue light LED + yellow phosphor technology path given in patent document 1 (Yoshinori Shimizu, Kensho Sakano, Yasunobu, Noguchi, Toshio Moriguchi, Light emitting device having a nitride compound semiconductor and a phosphor containing a garnetfluorescent material, US5998925A). However, due to the Y3Al5O 12 :Ce 3+The half-width of yellow phosphor is very large (>100 nm), resulting in a very small display color gamut, which can only reach ~70% NTSC. Therefore, this solution is usually only used in early and low-end display devices. As an improved technical solution, the technical solution of blue light LED + narrow-band green phosphor + narrow-band red phosphor can significantly expand the display color gamut of LCD devices. As disclosed in patent document 2 (Wang Jing, Liu Yong, Huang Lin, a high-performance narrow-band phosphor and its preparation method, CN109294565A), combining narrow-band red phosphor and narrow-band green phosphor with blue light chip can obtain a white light LED device with high lumen and wider color gamut. Therefore, this solution is also considered to be the mainstream packaging solution for wide color gamut LED backlight sources.

[0004] In the packaging solution based on pc-WLED, the quality of the luminescent material determines the quality of the LCD display device to a large extent. Many luminescent characteristics including the luminescent efficiency, luminescent thermal stability, grain surface morphology and emission half-width will affect the photoelectric efficiency, high-temperature reliability, screen resolution and color gamut of the packaged LED device. Among them, the development of high-performance narrow-band green phosphors is the core issue in promoting research related to wide color gamut LED displays. However, the currently disclosed narrow-band green phosphors still have problems such as low efficiency, poor thermal stability, large particle size and too wide emission spectrum, which greatly restricts the development of ultra-wide color gamut and ultra-high resolution LCD display devices. Currently, the most commonly used commercial narrow-band green luminescent material is β-Sialon: Eu 2+ Phosphor. As disclosed in patent document 3 (Takeda Yusuke, Nomiyama Tomohiro, Kobayashi Manabu, Watanabe Shintaro, β-sialon phosphor and light-emitting device, CN111936599A) and patent document 4 (Sakai Kenka, Kondo Yoshisuke, Nomiyama Tomohiro, Europium-activated β-sialon phosphor and light-emitting device, CN116018388A), the phosphor has high luminous efficiency and thermal stability, and a narrow emission spectrum. However, the phosphor generally exhibits a large particle size (>10 μm), and is therefore not suitable for direct use in LED backlight display devices. In addition, the luminescent material is not suitable for large-scale application in wide color gamut LED backlights. On this basis, as disclosed in Patent Document 5 (Zhou Tianliang, Gao Zhilong, A nitrogen oxide narrow-band green fluorescent material and preparation method and device, CN116590004A), Patent Document 6 (Zhou Tianliang, Ni Guoqin, A nitrogen oxide green fluorescent material and preparation method and device, CN118414404A) and Patent Document 7 (Wang Yuhua, Seto Xiaojun, Kang Runtian, A small-particle nitride narrow-band green phosphor and its preparation method, CN115093851A), Eu 2+ Other Nitrogen Oxides Doped with Narrow-Band Green Emitting Materials and β-Sialon: Eu 2+Phosphors belong to the same type of luminescent materials, which generally have high luminous efficiency, thermal stability and a wide color gamut. However, the conditions required for the preparation of this type of material are generally high, usually requiring a high temperature and high pressure environment for preparation, and high costs for raw materials and preparation. Therefore, it is not suitable for large-scale LCD display backlight applications.

[0005] In addition to nitrogen (oxide) compounds, Ce 3+ / Eu 2+ There are also many reports and patent documents on doped oxide luminescent materials such as aluminates, silicates, phosphates and borates. This type of material can avoid the high preparation conditions and production costs of nitrogen (oxide) compounds, and has high luminescence efficiency and thermal stability. However, this type of material usually has strong lattice coupling, which makes Ce 3+ / Eu 2+ The doping is manifested as a wider emission spectrum. Therefore, the display color gamut of the LCD device obtained by encapsulating this type of green light-emitting material is usually small. As disclosed in Patent Document 8 (Yang Zhiping, Mu Maolin, Liu Fang, Zhao Jinxin, A lutetium aluminate green phosphor and its preparation method and application, CN106590657A) and Patent Document 9 (Wang Qiuping, Huang Junyong, Tang Yong, A silicate green light-emitting material and its preparation method, CN102408890A), the emission half-width of these two materials is greater than 70 nm. Therefore, their color gamuts are relatively narrow and are not suitable for the preparation of wide color gamut LCD display devices.

[0006] Except Eu 2+ In addition to doped luminescent materials, more narrow-band green luminescent materials are studied with Mn 2+ As a luminescent ion. For example, Patent Document 10 (Zhu Yingli, Liang Yujun, Liu Shiqi, A UV-blue light excited aluminate-based narrow-band green phosphor and its preparation method, CN108949168A) and Patent Document 11 (Wang Yichao, Chen Baojiu, A Mn 2+ Activated β-Al2O3 narrow-band green phosphor and its preparation method, CN113956880A) disclosed that both materials have narrow emission spectrum, high color purity, excellent thermal stability, simple synthesis process and small particle size. However, Mn 2+ The luminous efficiency of doped narrow-band green phosphors is generally not high, especially the absorption rate in the ultraviolet-blue region is low, which makes their external quantum efficiency generally low. 2+ Doped narrow-band green luminescent materials are also not suitable for large-scale application in the preparation of wide color gamut LCD devices.

[0007] In addition, as disclosed in patent document 12 (Zhou Guojun, Ren Qiqiong, Zhang Xianming, a method for preparing ultrafast self-assembly of zero-dimensional manganese-based metal halide, CN113072928A) and patent document 13 (Wang Deyin, Lin Jie, Tao Yingfang, Hong Zifang, Guo Junlu, Wang Yuhua, a microwave-assisted liquid-phase synthesized narrow-band green phosphor and its synthesis method, CN112694888A), some narrow-band green luminescent materials choose metal halides as the research object. Compared with doped luminescent materials, this material usually has a simpler synthesis method and does not require high temperature sintering and other synthesis conditions. The obtained narrow-band green luminescent material has a higher luminescence quantum efficiency, a narrower luminescence spectrum and a wider color gamut. However, due to the presence of halogen elements, the thermal stability of this type of luminescent material is generally poor. At the normal operating temperature of LED backlight sources for displays (~150°C), its luminescent intensity has mostly dropped to less than 50% of the room temperature luminescent intensity. Therefore, it is not suitable for the preparation of wide color gamut LCD display devices.

[0008] From the above description, it can be seen that for LED backlight sources for ultra-wide color gamut LCD display devices, narrow-band green phosphors should have excellent luminescence properties in all aspects. However, most of the currently available materials cannot meet the usage requirements well.

[0009] It should be pointed out that Eu 2+ Doped gallium sulfide narrow-band green luminescent materials and their applications in display and lighting devices have been reported and disclosed in previous studies. For example, patent document 14 (Tian Yongchi, Diana Charomba, Perry Nair Yukon, High-efficiency phosphors based on alkaline earth metal thiogallates, CN101248155A) discloses a chemical formula of Sr 1-x Ca x Ga2S4:yEu 2+ ·zGa2S3 phosphor. The phosphor provided by the invention has an emission peak near 530 nm and high luminous efficiency. In addition, patent document 15 (Tian Yongchi, Diana Charomba, Perry Nair Youcon, Method and device for using high-efficiency phosphor based on alkaline earth metal thiogallate, CN1788067A) also discloses a light-emitting device prepared based on the light-emitting material and applicable to LCD display devices. However, the chemical formula protected by the invention only contains Sr and Ca elements and contains expensive Ga2S3 materials, so it is not suitable for large-scale preparation and application.

[0010] Patent document 16 (Yan Guosong, Yu Hao, Ci Hean, Li Jingmin, Tong Huanan, A rare earth doped thiogallate phosphor and preparation method, CN105219381A) discloses a chemical formula M 1-x Ga2S4: xR 2+, where M represents one or a combination of two of the alkaline earth metals Sr, Ca, Ba or Mg. The luminescent material can achieve narrow-band green light emission under blue light excitation and can be used for the packaging of display screens of display devices. However, the chemical formula protected by the invention does not include the Zn element, and the luminescent quantum efficiency of the material under the excitation conditions of purple light / blue light does not reach a very high level.

[0011] In addition, it should be noted that according to non-patent document 1 (Tagiev, BG, Guseinov, GG,Dzhabbarov, RB, Tagiev, OB, Musaeva, NN, & Georgobiani, AN (2000). Synthesis and luminescent properties of ZnGa2S4: Eu, F and ZnGa2O4:Eu, F. Inorganic materials, 36(12), 1189-1191), non-patent document 2 (Cho, YS, & Huh,YD (2017). Photoluminescence Characteristics of Green-emitting ZnGa2S4: Euand EuGa2S4 Phosphors. Bulletin of the Korean Chemical Society, 38(4), 493-498) and non-patent document 3 (Yu, R., Luan, R., Wang, C., Chen, J., Wang, Z., Moon, BK, & Jeong, JH (2012). Photoluminescence properties of green-emittingZnGa2S4: Eu 2+phosphor. Journal of the Electrochemical Society, 159(5), J188) pointed out that the emission wavelength of ZnGa2S4:Eu phosphor is at 540 nm, while its excitation spectrum is mostly in the violet / blue region (380~480 nm), and its absorption of ultraviolet light is poor. In addition, the internal / external quantum efficiency of this luminescent material under various light excitations is low, and the grain size is generally large (~5-10 μm), so it is not suitable for direct application in wide color gamut LCD display devices. Non-patent document 4 (Jabbarov, RB, Chartier, C., Tagiev, BG, Tagiev, OB,Musayeva, NN, Barthou, C., & Bénalloul, P. (2005). Radiative properties ofEu 2+ in BaGa2S4. Journal of Physics and Chemistry of Solids, 66(6), 1049-1056) and non-patent document 5 (Georgobiani, AN, Tagiev, BG, Abushov, SA, Tagiev, OB, Xu, Z., & Zhao, S. (2008). Photo-and thermoluminescence of BaGa2S4:Eu 2+ and BaGa2S4:Eu 2+ ,Ce 3+ crystals. Inorganic Materials, 44, 110-114) pointed out that the chemical formula is BaGa2S4:Eu 2+ The emission wavelength of the phosphor is 490~500 nm, and the half-width of the emission spectrum is relatively large (~70 nm). Therefore, this luminescent material is generally considered to be a cyan luminescent material, and the color gamut of the LED device obtained by sample packaging is relatively narrow. In addition, the material has a low absorption rate for blue light, so it is not suitable for preparing LCD backlight luminescent devices with a wide color gamut in combination with blue LED chips.

[0012] Furthermore, in Eu 2+In activated gallium sulfide phosphors, it is common to use different metal elements to improve the original chemical formula. However, with the change of solid solution components, the intensity and comprehensive performance of its emission spectrum usually only show regular changes. For example, non-patent document 6 (Ko, K., Huh, Y., & Do, YR (2008).Cathodoluminescence and Longevity Properties of Potential Sr 1-x M x Ga2S4:Eu(M =Ba or Ca) Green Phosphors for Field Emission Displays. BULLETIN-KOREANCHEMICAL SOCIETY, 29(4), 822), original SrGa2S4:Eu 2+ The component has high luminescence efficiency but the emission peak is reddish (~530 nm). For the solid solution component Sr / Ba, as the Ba content increases, the main peak position of the emission spectrum can be monotonically blue-shifted, but it is also accompanied by a gradual decrease in the luminescence intensity. For the solid solution component Sr / Ca, as the Ca content increases, the main peak position of the emission spectrum gradually red-shifts, accompanied by a rapid decrease in the luminescence intensity; Non-patent document 7 (Leanenia, MS, Lutsenko, EV, Rzheutskij, NV, Pavlovskii, VN, Yablonskii, GP, Nagiev, TG, Tagiev, BG, Abushev, SA, Tagiev, OB (2015). Photoluminescence of Ca x Ba 1–x Ga2S4 Solid Solutions Activated by Eu 2+ Ions.Journal of Applied Spectroscopy, 82, 248-253), for the original BaGa2S4: Eu 2+ As the solid solution content of Ca increases, the luminescence of the sample gradually shifts from cyan to yellow, and there are green luminescent components in the solid solution. However, the increase in solid solution concentration is also accompanied by a decrease in luminescence intensity.

[0013] In summary, it can be seen from the existing public literature that there is a great lack of luminescent materials that can simultaneously emit narrow-band green light under wide-spectrum excitation of ultraviolet / purple / blue light, have high luminescence quantum efficiency, wide color gamut, good thermal stability, small grain size, and simple preparation methods. Compared with the reported / public materials such as nitrides (oxygen) compounds, oxides, and halides, Eu 2+ Doped gallium sulfide materials have good comprehensive luminescence performance, but the existing publicly available materials still have a lot of room for improvement in terms of luminescence quantum efficiency, luminescence bandwidth and color gamut width. Therefore, the development of a new chemical composition, divalent europium-activated zinc barium gallium sulfide green luminescent material is crucial to realize the packaging and application of wide color gamut LED backlight devices. Summary of the invention

[0014] The purpose of the present invention is to protect a divalent europium activated zinc barium gallium sulfide green luminescent material and a preparation method and application thereof.

[0015] The present invention provides a divalent europium activated zinc barium gallium sulfide green light-emitting material, the chemical general formula of the divalent europium activated zinc barium gallium sulfide green light-emitting material is ZnBa2Ga6S 12 : Eu 2+ , where Eu 2+ As doping ions into the crystal lattice. Further, according to Eu 2+ The doping ions enter the lattice at different positions. The general chemical formula contains two series: Eu x Zn 1-x Ba2Ga6S 12 and Eu y ZBZ 2-y Ga6S 12 , among which, 0.04≤x≤0.47; 0.05≤y≤0.54.

[0016] Furthermore, the excitation spectrum of the luminescent material can cover a wide absorption band of 280~480 nm. Under the excitation of ultraviolet light / violet light / blue light, the main emission peak range of the luminescent material is between 505~530 nm, which is located in the green region; under the excitation of near-ultraviolet / violet light (340~420 nm), the best luminescence internal / external quantum efficiency of the luminescent material is not less than 75% / 55%; under the excitation of blue light (420~460 nm), the best luminescence internal / external quantum efficiency is not less than 55% / 35%; in addition, the average grain size of the luminescent material is about 3-5 μm, the particles are evenly distributed, and the surface morphology is good.

[0017] The present invention also provides a method for preparing the divalent europium activated zinc barium gallium sulfide green light-emitting material as described above, the preparation method comprising the following steps: (1) mixing a Eu precursor, a Zn precursor, a Ba precursor, a Ga precursor and an S precursor to obtain a mixture; the precursor is an oxide, a sulfide, a carbonate or a single substance; (2) subjecting the mixture to a high-temperature solid-phase reaction in a reducing atmosphere containing sulfur vapor to obtain the divalent europium activated zinc barium gallium sulfide green light-emitting material.

[0018] Furthermore, in step (1), in Eu x Zn 1-x Ba2Ga6S 12 In the series, the molar ratio of Eu, Zn, Ba, Ga and S in the precursor is x: (1-x): 2: 6: 19.2. Since the melting point and boiling point of S powder are both low, in order to avoid the loss of sulfur element during high temperature sintering, the amount of S precursor added is 1.6 times the stoichiometric ratio; y ZBZ 2-y Ga6S 12 In the series, the molar ratio of Eu, Zn, Ba, Ga and S in the precursor is y:1:(2-y):6:19.2. Similarly, the amount of S precursor added is 1.6 times the stoichiometric ratio.

[0019] Further, in step (1), the Eu precursor is selected from one or more of Eu oxide, Eu sulfide or Eu nitrate; the Zn precursor is selected from one or more of Zn oxide, Zn sulfide or Zn nitrate; the Ba precursor is selected from one or more of Ba carbonate, Ba oxide, Ba sulfide or Ba nitrate; the Ga precursor is selected from one or more of Ga oxide or Ga sulfide; the S precursor is selected from sublimation sulfur powder or precipitation sulfur powder, and the purity of the Zn precursor, Ba precursor, Eu precursor and Ga precursor is not less than 99.5wt%. The purity of the sublimation sulfur powder or precipitation sulfur powder is not less than 99%.

[0020] Furthermore, in step (2), in order to ensure that the reaction product is fully sulfurized and avoid the presence of oxide impurities, the mixture needs to be subjected to a high-temperature solid phase reaction in a sulfur-containing reducing atmosphere. The temperature of the high-temperature solid phase reaction is 800-1000°C, and the time of the high-temperature solid phase reaction is 2-6 hours.

[0021] Furthermore, in step (2), the reducing atmosphere of the high-temperature solid-phase reaction is hydrogen sulfide gas or a nitrogen-hydrogen mixture containing sulfur vapor. If a nitrogen-hydrogen mixture containing sulfur vapor is used, the volume content of hydrogen is 10-25%, and the volume content of sulfur vapor is 5-10%. The gas flow rate during the whole preparation process is not less than 200 ml / min. With the help of the method of sulfide atmosphere-assisted reaction, the phase purity and comprehensive luminescence performance of the product can be further improved.

[0022] The present invention also provides an application of the divalent europium-activated zinc barium gallium sulfide green light-emitting material in display and lighting devices. The lighting device uses the divalent europium-activated zinc barium gallium sulfide green light-emitting material as a luminescence conversion substance. The luminescence conversion substance contains the divalent europium-activated zinc barium gallium sulfide green light-emitting material. The luminescence conversion substance is excited by a near-ultraviolet / purple / blue light LED to emit green light.

[0023] Furthermore, the display and lighting device uses near-ultraviolet light / purple light / blue light LED with a main emission wavelength peak at 365-460 nm as an excitation source.

[0024] Furthermore, the display and lighting device is a white light LED device, and its color gamut is not less than 80% NTSC. The typical display index (R1-R8) and special color rendering index (R9-R15) of the full-spectrum white light lighting device are both greater than 99.

[0025] The key points of the present invention are:

[0026] 1. Compared with patent documents 3, 4, 5, 6, and 7, the preparation method provided by the present invention is simple and easy to implement, the raw materials are cheap and readily available, and the grains of the obtained material are evenly dispersed and small in size;

[0027] 2. Compared with patent documents 8 and 9, the present invention can achieve an emission spectrum with a narrower half-width, and thus can effectively encapsulate an LED backlight device for wide color gamut display;

[0028] 3. Compared with patent documents 10 and 11, the present invention has a high absorption efficiency for ultraviolet light / purple light / blue light, thereby achieving high internal / external quantum efficiency of luminescence;

[0029] 4. Compared with patent documents 12 and 13, the present invention has higher luminescence thermal stability and better chemical stability, and therefore has good practicality;

[0030] 5. Compared with patent documents 14, 16 and non-patent documents 1-7, the divalent europium activated zinc barium gallium sulfide green light-emitting material provided by the present invention has a completely new chemical composition and unique light-emitting properties.

[0031] Beneficial Effects

[0032] The present invention provides a divalent europium activated zinc barium gallium sulfide green luminescent material and a preparation method and application thereof. The chemical general formula of the divalent europium activated zinc barium gallium sulfide green luminescent material is ZnBa2Ga6S 12 : Eu 2+ , further, the chemical formula contains two series: Eu x Zn 1-x Ba2Ga6S 12 and Eu y ZBZ 2-y Ga6S 12 , wherein 0.04≤x≤0.47; 0.05≤y≤0.54. Under the excitation of ultraviolet light / purple light / blue light, the main peak range of the emission wavelength generated by the green luminescent material is between 505 and 530 nm.

[0033] Compared with oxide materials, the lattice coupling degree of sulfide materials is generally smaller, so it is easier to achieve narrow-band green luminescence (~510 nm); compared with halide materials, this type of compound has better luminescence thermal stability; and compared with nitrogen (oxy) compound luminescent materials, this type of compound can well avoid the problems of difficult preparation technology and high raw material cost. This material has a new chemical composition, good luminescence thermal stability, small and dispersed grain particles (3-5 μm), and high luminescence internal and external quantum efficiency under ultraviolet light, purple light (>75% / 55%) and blue light (>55% / 35%) excitation. As a result, this luminescent material is used in wide color gamut LCD display and high color rendering quality full spectrum lighting devices. The LCD display device prepared using this compound can have ultra-high definition resolution and a wider color gamut range (NTSC>80%). This material is also suitable for the preparation and application of full-spectrum LED devices with ultra-high color rendering quality. The typical display index (R1~R8) and special color rendering index (R9~R15) of the obtained full-spectrum white light LED device are both greater than 99. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 Spectra of the luminescent material obtained in Example 4 of the present invention, wherein (a) is an excitation spectrum and (b) is an emission spectrum;

[0036] Figure 2Spectra of the luminescent material obtained in Example 5 of the present invention, wherein (a) is an excitation spectrum and (b) is an emission spectrum;

[0037] Figure 3 Spectra of the luminescent material obtained in Example 10 of the present invention, wherein (a) is an excitation spectrum and (b) is an emission spectrum;

[0038] Figure 4 The quantum efficiency spectrum of the luminescent material obtained in Example 4 of the present invention, wherein the excitation light wavelength of (a) is 400 nm, and the excitation light wavelength of (b) is 450 nm;

[0039] Figure 5 This is a scanning electron microscope image of the luminescent material obtained in Example 4 of the present invention;

[0040] Figure 6 The temperature-dependent test results of the luminescent material obtained in Example 4 of the present invention, wherein (a) is a temperature-dependent emission spectrum diagram, and (b) is a temperature-dependent luminescence intensity curve diagram;

[0041] Figure 7 This is an electroluminescence spectrum diagram of the LED device obtained in Example 13 of the present invention;

[0042] Figure 8 This is an electroluminescence spectrum diagram of the LED device obtained in Example 14 of the present invention;

[0043] Fig. 9 This is the electroluminescence spectrum of the LED device obtained in Example 15 of the present invention. DETAILED DESCRIPTION

[0044] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0045] The present invention provides a divalent europium activated zinc barium gallium sulfide green light-emitting material, the general chemical formula of which is as follows:

[0046] ZnBa2Ga6S 12 : Eu 2+

[0047] Among them, Eu 2+ As doping ions into the crystal lattice. Further, according to Eu 2+ The doping ions enter the lattice at different positions. The general chemical formula can contain two series: Eu x Zn 1-x Ba2Ga6S 12 and Eu y ZBZ 2-y Ga6S 12, wherein 0.04≤x≤0.47; 0.05≤y≤0.54. In some embodiments of series 1 provided by the present invention, x is preferably 0.04, 0.16, 0.24, 0.31, 0.40 and 0.47; in some embodiments of series 2 provided by the present invention, y is preferably 0.05, 0.15, 0.22, 0.32, 0.45 and 0.54;

[0048] The present invention also provides a method for preparing the divalent europium activated zinc barium gallium sulfide green light-emitting material, the specific steps of which are as follows:

[0049] Eu precursor, Zn precursor, Ba precursor, Ga precursor and S precursor are mixed, and a high-temperature solid-phase reaction is carried out in a reducing atmosphere containing sulfur vapor to obtain a divalent europium-activated zinc-barium-gallium sulfide green luminescent material.

[0050] In the steps, in Eu x Zn 1-x Ba2Ga6S 12 In the series, the molar ratio of Eu, Zn, Ba, Ga and S in the precursor is x: (1-x): 2: 6: 19.2; in order to offset the burnout of the low melting point and low boiling point sulfur precursor, the amount of S precursor added needs to be 1.6 times the stoichiometric ratio; y ZBZ 2-y Ga6S 12 In the series, the molar ratio of Eu, Zn, Ba, Ga and S in the precursor is y:1:(2-y):6:19.2; similarly, the amount of S precursor added also needs to be 1.6 times the stoichiometric ratio.

[0051] In the steps, the Eu precursor is selected from one or more of Eu oxide, Eu sulfide or Eu nitrate, more preferably Eu oxide (i.e. europium oxide); the Zn precursor is selected from one or more of Zn oxide, Zn sulfide and Zn nitrate, more preferably Zn sulfide (i.e. zinc sulfide); the Ba precursor is selected from one or more of Ba carbonate, Ba oxide, Ba sulfide or Ba nitrate; more preferably Ba carbonate (i.e. barium carbonate); the Ga precursor is selected from one or more of Ga oxide or Ga sulfide, more preferably Ga oxide (i.e. gallium oxide); the S precursor is one or more of sublimated sulfur powder or precipitated sulfur powder, more preferably sublimated sulfur powder.

[0052] The purity of the Eu precursor, Zn precursor, Ba precursor, and Ga precursor is not less than 99.5wt%, and the purity of the S precursor is not less than 99%wt. The higher the purity, the less impurities in the obtained luminescent material.

[0053] The reducing atmosphere in the step can be a dry atmosphere well known to those skilled in the art, such as hydrogen sulfide or nitrogen-hydrogen mixture, to ensure that the reaction product is fully sulfurized and avoid the presence of oxide impurities. If a nitrogen-hydrogen mixture is used, a certain volume ratio (5-10%) of sulfur vapor needs to be mixed into the original atmosphere, and the hydrogen content needs to be maintained at a volume content of 10-20%. In addition, a hydrogen sulfide atmosphere can also be selected, and no additional sulfur needs to be mixed in at this time. In the present invention, a nitrogen-hydrogen mixture is preferred. Preferably, in the nitrogen-hydrogen mixture containing sulfur vapor, the volume content of hydrogen is 15%, and the volume content of sulfur vapor is 5%.

[0054] In the step, the gas flow rate of the reducing atmosphere during the sintering process should be no less than 200 ml / min. In some embodiments provided by the present invention, the flow rate of the sulfur-containing nitrogen and hydrogen mixed gas is preferably 250 ml / min.

[0055] The temperature of the high temperature solid phase reaction in the step is 800-1000° C. In some embodiments provided by the present invention, the temperature of the high temperature solid phase reaction is preferably 900° C. The time of the high temperature solid phase reaction in the step is 2-6 h; in some embodiments provided by the present invention, the time of the high temperature solid phase reaction is preferably 3 h.

[0056] The high temperature solid phase reaction is preferably carried out in a high temperature furnace. After the reaction is carried out, the furnace is cooled to room temperature to obtain a divalent europium activated zinc barium gallium sulfide green light emitting material.

[0057] The lighting device made of the divalent europium activated zinc barium gallium sulfide green luminescent material is composed of at least ultraviolet light / purple light / blue light LED and luminescent conversion material. The chemical formula of the luminescent conversion material is: ZnBa2Ga6S 12 :Eu 2+ Divalent europium-activated zinc barium gallium sulfide green light-emitting material.

[0058] In order to further illustrate the present invention, a divalent europium activated zinc barium gallium sulfide green light-emitting material and a preparation method thereof provided by the present invention are described in detail below in conjunction with examples.

[0059] The reagents used in the following examples are all commercially available.

[0060] The luminescence quantum efficiency of the luminescent material was tested using an integrating sphere and a spectral measuring instrument. The test temperature was room temperature (~25°C). The excitation wavelengths were fixed at 400 nm and 450 nm. The luminescence quantum efficiency test was performed with Al2O3 powder (commercially available, 99.99 wt% pure, d 90<3 μm) as a reference sample. Among them, the internal quantum efficiency of luminescence is defined as the ratio of the number of photons emitted by the material to the number of photons absorbed at the selected excitation wavelength; the external quantum efficiency of luminescence is defined as the ratio of the number of photons emitted by the material to the number of incident photons at the selected excitation wavelength. Luminescence quantum efficiency is one of the most important indicators for evaluating the comprehensive performance of luminescent materials. It is generally believed that for actual LED device applications, the external quantum efficiency of luminescent materials is more important than the internal quantum efficiency, and the standard for evaluating the high external quantum efficiency of materials usually requires more than 50%.

[0061] The scanning electron microscope (JSM-6510A, JEOL Ltd.) was used to take photos and analyze the microscopic morphology of the luminescent material. It is generally believed that for narrow-band luminescent materials used in display LEDs, the average particle size of the material is usually required to be no more than 5 microns.

[0062] The variable temperature accessory is used with a spectrum measuring instrument to test the thermal stability of the luminescent material. The test temperature range is 20℃-140℃, and the excitation wavelength is fixed at 450nm. It is generally believed that for actual LED device applications, the operating temperature of the phosphor layer can reach above 130℃. Therefore, the definition of good thermal stability of luminescent materials usually requires that the luminous intensity of the sample at around 130℃ can still maintain more than half of the luminous intensity at room temperature.

[0063] The electroluminescence spectrum of the LED device was tested using a high-precision fast spectroradiometer connected to an integrating sphere. The test temperature was room temperature (~25°C). The test voltage was kept at around 6.5 V, and the test currents were 20 mA, 60 mA, 100 mA, 140 mA, 180 mA, 220 mA, 260 mA, and 300 mA.

[0064] In the nitrogen and hydrogen mixed atmosphere used in the following examples, the volume content of hydrogen is 15%, and the volume content of sulfur vapor is 5%.

[0065] The Eu precursor, Zn precursor, Ba precursor, Ga precursor and S precursor used in the embodiment are only examples and do not constitute a limitation on the precursor raw materials. Except for the S precursor, the purity of all precursors is not less than 99.5wt%; the purity of the S precursor is not less than 99wt%.

[0066] Example 1

[0067] The material described in this embodiment is series 1, which contains the chemical formula of the compound: Eu 0.04 Zn 0.96 Ba2Ga6S 12Eu2O3, ZnS, BaCO3, Ga2O3 and sublimed sulfur powder were used as raw materials. The raw materials were accurately weighed according to the molar ratio of Eu, Zn, Ba, Ga and S of 0.04:0.96:2:6:19.2, and sintered at 900°C in a mixed atmosphere of nitrogen (80% volume) + hydrogen (15% volume) + sulfur vapor (5% volume) for 3 h. After cooling, a product with a nominal chemical composition of Eu2O3 was obtained. 0.04 Zn 0.96 Ba2Ga6S 12 The emission spectrum and quantum efficiency of the obtained luminescent material were measured using a fluorescence spectrometer and an integrating sphere, and the test results are shown in Table 1. As can be seen from Table 1, the main peak of the emission spectrum of the material obtained in Example 1 is located near 525 nm. Under 400 nm violet light excitation, the internal / external quantum efficiency of the material is 68.6% / 51.2%; under 450 nm blue light excitation, the internal / external quantum efficiency of the material is 51.8% / 31.4%. It can be seen that the material obtained in Example 1 is a divalent europium activated zinc barium gallium sulfide green luminescent material.

[0068] Example 2

[0069] The material described in this embodiment is series 1, which contains the chemical formula of the compound: Eu 0.16 Zn 0.84 Ba2Ga6S 12 Eu2O3, ZnS, BaCO3, Ga2O3 and sublimed sulfur powder were used as raw materials. The raw materials were accurately weighed according to the molar ratio of Eu, Zn, Ba, Ga and S of 0.16:0.84:2:6:19.2, and sintered at 900°C in a mixed atmosphere of nitrogen (80% volume) + hydrogen (15% volume) + sulfur vapor (5% volume) for 3 h. After cooling, a material with a nominal chemical composition of Eu2O3 was obtained. 0.16 Zn 0.84 Ba2Ga6S 12 The emission spectrum and quantum efficiency of the obtained luminescent material were measured using a fluorescence spectrometer and an integrating sphere, and the test results are shown in Table 1. As can be seen from Table 1, the main peak of the emission spectrum of the material obtained in Example 2 is located near 522 nm. Under 400 nm violet light excitation, the internal / external quantum efficiency of the material is 69.8% / 52.8%; under 450 nm blue light excitation, the internal / external quantum efficiency of the material is 52.4% / 32.2%. It can be seen that the material obtained in Example 2 is a divalent europium activated zinc barium gallium sulfide green luminescent material.

[0070] Example 3

[0071] The material described in this embodiment is series 1, which contains the chemical formula of the compound: Eu 0.24 Zn 0.76Ba2Ga6S 12 Eu2O3, ZnS, BaCO3, Ga2O3 and sublimed sulfur powder were used as raw materials. The raw materials were accurately weighed according to the molar ratio of Eu, Zn, Ba, Ga and S of 0.24:0.76:2:6:19.2, and sintered at 900°C in a mixed atmosphere of nitrogen (80% volume) + hydrogen (15% volume) + sulfur vapor (5% volume) for 3 h. After cooling, a material with a nominal chemical composition of Eu2O3 was obtained. 0.24 Zn 0.76 Ba2Ga6S 12 The emission spectrum and quantum efficiency of the obtained luminescent material were measured using a fluorescence spectrometer and an integrating sphere, and the test results are shown in Table 1. As can be seen from Table 1, the main peak of the emission spectrum of the material obtained in Example 3 is located near 520 nm. Under 400 nm violet light excitation, the internal / external quantum efficiency of the material is 70.1% / 53.6%; under 450 nm blue light excitation, the internal / external quantum efficiency of the material is 53.6% / 33.3%. It can be seen that the material obtained in Example 3 is a divalent europium activated zinc barium gallium sulfide green luminescent material.

[0072] Example 4

[0073] The material described in this embodiment is series 1, which contains the chemical formula of the compound: Eu 0.31 Zn 0.69 Ba2Ga6S 12 Eu2O3, ZnS, BaCO3, Ga2O3 and sublimed sulfur powder were used as raw materials. The raw materials were accurately weighed according to the molar ratio of Eu, Zn, Ba, Ga and S of 0.31:0.69:2:6:19.2, and sintered at 900°C in a mixed atmosphere of nitrogen (80% volume) + hydrogen (15% volume) + sulfur vapor (5% volume) for 3 h. After cooling, a material with a nominal chemical composition of Eu2O3 was obtained. 0.31 Zn 0.69 Ba2Ga6S 12 The emission spectrum and quantum efficiency of the obtained luminescent material were measured using a fluorescence spectrometer and an integrating sphere. The steady-state spectrum test results are shown in Figure 1 and Table 1. Figure 1 (a) It can be seen that the excitation spectrum of the material prepared in Example 4 can cover a wide range of 280-480 nm. Figure 1 (b), the main peak of the emission spectrum of the material is located near 517 nm. The test results of quantum efficiency are shown in Figure 4 As shown, Figure 4 (a) shows that under 400 nm violet light excitation, the internal / external quantum efficiency of the material is 70.3% / 55.0%; Figure 4(b) shows that under 450 nm blue light excitation, the internal / external quantum efficiency of the material is 55.8% / 34.9%. It can be seen that the material obtained in Example 4 is a divalent europium-activated zinc barium gallium sulfide green light-emitting material, and it has a high internal / external quantum efficiency of light emission. In addition, Figure 5 The scanning electron microscope morphology of the material obtained in this embodiment is also shown. According to the photos and analysis, the average particle size of the material is about 4 microns, indicating that the material has a smaller particle size, which is more conducive to the application of white light LEDs for display. Figure 6 (a) is the temperature-dependent emission spectrum of the material. Figure 6 As shown in the results (b), under 450 nm light excitation, the luminescence intensity of the material obtained in this example at 140°C can still maintain 75.4% of the luminescence intensity at room temperature (~20°C), which shows that the material has good luminescence thermal stability.

[0074] Example 5

[0075] The material described in this embodiment is series 1, which contains the chemical formula of the compound: Eu 0.40 Zn 0.60 Ba2Ga6S 12 Eu2O3, ZnS, BaCO3, Ga2O3 and sublimed sulfur powder were used as raw materials. The raw materials were accurately weighed according to the molar ratio of Eu, Zn, Ba, Ga and S of 0.40:0.60:2:6:19.2, and sintered at 900°C in a mixed atmosphere of nitrogen (80% volume) + hydrogen (15% volume) + sulfur vapor (5% volume) for 3 h. After cooling, a material with a nominal chemical composition of Eu2O3 was obtained. 0.40 Zn 0.60 Ba2Ga6S 12 The emission spectrum and quantum efficiency of the obtained luminescent material were measured using a fluorescence spectrometer and an integrating sphere. The steady-state spectrum test results are shown in Figure 2 and Table 1. Figure 2 (a) It can be seen that the excitation spectrum of the material prepared in Example 5 can cover a wide range of 280-480 nm. Figure 2 (b), the main peak of the emission spectrum of the material is located near 513 nm. Under 400 nm violet light excitation, the internal / external quantum efficiency of the material is 75.1% / 56.5%; under 450 nm blue light excitation, the internal / external quantum efficiency of the material is 55.2% / 34.1%. It can be seen that the material obtained in Example 5 is a divalent europium-activated zinc barium gallium sulfide green light-emitting material, and it has a high internal / external quantum efficiency of light emission.

[0076] Example 6

[0077] The material described in this embodiment is series 1, which contains the chemical formula of the compound: Eu 0.47 Zn 0.53 Ba2Ga6S 12 Eu2O3, ZnS, BaCO3, Ga2O3 and sublimed sulfur powder were used as raw materials. The raw materials were accurately weighed according to the molar ratio of Eu, Zn, Ba, Ga and S of 0.47:0.53:2:6:19.2. The raw materials were sintered at 900°C in a mixed atmosphere of nitrogen (80% volume) + hydrogen (15% volume) + sulfur vapor (5% volume) for 3 h. After cooling, a material with a nominal chemical composition of Eu2O3 was obtained. 0.47 Zn 0.53 Ba2Ga6S 12 The emission spectrum and quantum efficiency of the obtained luminescent material were measured using a fluorescence spectrometer and an integrating sphere, and the test results are shown in Table 1. As can be seen from Table 1, the main peak of the emission spectrum of the material obtained in Example 6 is located near 507 nm. Under 400 nm violet light excitation, the internal / external quantum efficiency of the material is 74.3% / 57.4%; under 450 nm blue light excitation, the internal / external quantum efficiency of the material is 54.5% / 33.7%. It can be seen that the material obtained in Example 6 is a divalent europium-activated zinc barium gallium sulfide green luminescent material, and it has a high internal / external quantum efficiency of luminescence.

[0078] Example 7

[0079] The material described in this embodiment is series 2, and the chemical formula of the compound contained therein is: Eu 0.05 ZBZ 1.95 Ga6S 12 Eu2O3, ZnS, BaCO3, Ga2O3 and sublimed sulfur powder were used as raw materials. The raw materials were accurately weighed according to the molar ratio of Eu, Zn, Ba, Ga and S of 0.05:1:1.95:6:19.2. The raw materials were sintered at 900°C in a mixed atmosphere of nitrogen (80% volume) + hydrogen (15% volume) + sulfur vapor (5% volume) for 3 h. After cooling, a material with a nominal chemical composition of Eu2O3 was obtained. 0.05 ZBZ 1.95 Ga6S 12 The emission spectrum and quantum efficiency of the obtained luminescent material were measured using a fluorescence spectrometer and an integrating sphere, and the test results are shown in Table 1. As can be seen from Table 1, the main peak of the emission spectrum of the material obtained in Example 7 is located near 520 nm. Under 400 nm violet light excitation, the internal / external quantum efficiency of the material is 70.0% / 52.2%; under 450 nm blue light excitation, the internal / external quantum efficiency of the material is 51.9% / 31.4%. It can be seen that the material obtained in Example 7 is a divalent europium activated zinc barium gallium sulfide green luminescent material.

[0080] Example 8

[0081] The material described in this embodiment is series 2, and the chemical formula of the compound contained therein is: Eu 0.15 ZBZ 1.85 Ga6S 12 Eu2O3, ZnS, BaCO3, Ga2O3 and sublimed sulfur powder were used as raw materials. The raw materials were accurately weighed according to the molar ratio of Eu, Zn, Ba, Ga and S of 0.15:1:1.85:6:19.2. The raw materials were sintered at 900°C in a mixed atmosphere of nitrogen (80% volume) + hydrogen (15% volume) + sulfur vapor (5% volume) for 3 h. After cooling, a product with a nominal chemical composition of Eu2O3 was obtained. 0.15 ZBZ 1.85 Ga6S 12 The emission spectrum and quantum efficiency of the obtained luminescent material were measured using a fluorescence spectrometer and an integrating sphere, and the test results are shown in Table 1. As can be seen from Table 1, the main peak of the emission spectrum of the material obtained in Example 8 is located near 522 nm. Under 400 nm violet light excitation, the internal / external quantum efficiency of the material is 71.2% / 53.5%; under 450 nm blue light excitation, the internal / external quantum efficiency of the material is 52.7% / 32.9%. It can be seen that the material obtained in Example 8 is a divalent europium activated zinc barium gallium sulfide green luminescent material.

[0082] Example 9

[0083] The material described in this embodiment is series 2, and the chemical formula of the compound contained therein is: Eu 0.22 ZBZ 1.78 Ga6S 12 Eu2O3, ZnS, BaCO3, Ga2O3 and sublimed sulfur powder were used as raw materials. The raw materials were accurately weighed according to the molar ratio of Eu, Zn, Ba, Ga and S of 0.22:1:1.78:6:19.2. The raw materials were sintered at 900°C in a mixed atmosphere of nitrogen (80% volume) + hydrogen (15% volume) + sulfur vapor (5% volume) for 3 h. After cooling, a product with a nominal chemical composition of Eu2O3 was obtained. 0.22 ZBZ 1.78 Ga6S 12The emission spectrum and quantum efficiency of the obtained luminescent material were measured using a fluorescence spectrometer and an integrating sphere, and the test results are shown in Table 1. As can be seen from Table 1, the main peak of the emission spectrum of the material obtained in Example 9 is located near 524 nm. Under 400 nm violet light excitation, the internal / external quantum efficiency of the material is 72.4% / 54.3%; under 450 nm blue light excitation, the internal / external quantum efficiency of the material is 53.5% / 33.6%. It can be seen that the material obtained in Example 9 is a divalent europium-activated zinc barium gallium sulfide green luminescent material, and it has a high internal / external quantum efficiency of luminescence.

[0084] Example 10

[0085] The material described in this embodiment is series 2, and the chemical formula of the compound contained therein is: Eu 0.32 ZBZ 1.68 Ga6S 12 Eu2O3, ZnS, BaCO3, Ga2O3 and sublimed sulfur powder were used as raw materials. The raw materials were accurately weighed according to the molar ratio of Eu, Zn, Ba, Ga and S of 0.32:1:1.68:6:19.2. The raw materials were sintered at 900°C in a mixed atmosphere of nitrogen (80% volume) + hydrogen (15% volume) + sulfur vapor (5% volume) for 3 h. After cooling, a product with a nominal chemical composition of Eu2O3 was obtained. 0.32 ZBZ 1.68 Ga6S 12 The emission spectrum and quantum efficiency of the obtained luminescent material were measured using a fluorescence spectrometer and an integrating sphere. The test results are shown in Figure 3 and Table 1. Figure 3 (a) It can be seen that the excitation spectrum of the material prepared in Example 10 can cover a wide range of 280-480 nm. Figure 3 (b), the main peak of the emission spectrum of the material is located near 527 nm. Under 400 nm violet light excitation, the internal / external quantum efficiency of the material is 71.8% / 53.6%; under 450 nm blue light excitation, the internal / external quantum efficiency of the material is 54.8% / 34.9%. It can be seen that the material obtained in Example 10 is a divalent europium-activated zinc barium gallium sulfide green light-emitting material, and it has a high internal / external quantum efficiency of light emission.

[0086] Embodiment 11

[0087] The material described in this embodiment is series 2, and the chemical formula of the compound contained therein is: Eu 0.45 ZBZ 1.55 Ga6S 12Eu2O3, ZnS, BaCO3, Ga2O3 and sublimed sulfur powder were used as raw materials. The raw materials were accurately weighed according to the molar ratio of Eu, Zn, Ba, Ga and S of 0.45:1:1.55:6:19.2. The raw materials were sintered at 900°C in a mixed atmosphere of nitrogen (80% volume) + hydrogen (15% volume) + sulfur vapor (5% volume) for 3 h. After cooling, a product with a nominal chemical composition of Eu2O3 was obtained. 0.45 ZBZ 1.55 Ga6S 12 The emission spectrum and quantum efficiency of the obtained luminescent material were measured using a fluorescence spectrometer and an integrating sphere, and the test results are shown in Table 1. As can be seen from Table 1, the main peak of the emission spectrum of the material obtained in Example 11 is located near 529 nm. Under 400 nm violet light excitation, the internal / external quantum efficiency of the material is 70.9% / 52.4%; under 450 nm blue light excitation, the internal / external quantum efficiency of the material is 55.4% / 35.5%. It can be seen that the material obtained in Example 11 is a divalent europium activated zinc barium gallium sulfide green luminescent material.

[0088] Example 12

[0089] The material described in this embodiment is series 2, and the chemical formula of the compound contained therein is: Eu 0.54 ZBZ 1.46 Ga6S 12 Eu2O3, ZnS, BaCO3, Ga2O3 and sublimed sulfur powder were used as raw materials. The raw materials were accurately weighed according to the molar ratio of Eu, Zn, Ba, Ga and S of 0.54:1:1.46:6:19.2. The raw materials were sintered at 900°C in a mixed atmosphere of nitrogen (80% volume) + hydrogen (15% volume) + sulfur vapor (5% volume) for 3 h. After cooling, a material with a nominal chemical composition of Eu2O3 was obtained. 0.54 ZBZ 1.46 Ga6S 12 The emission spectrum and quantum efficiency of the obtained luminescent material were measured using a fluorescence spectrometer and an integrating sphere, and the test results are shown in Table 1. As can be seen from Table 1, the main peak of the emission spectrum of the material obtained in Example 12 is located near 533 nm. Under 400 nm violet light excitation, the internal / external quantum efficiency of the material is 70.2% / 51.2%; under 450 nm blue light excitation, the internal / external quantum efficiency of the material is 56.1% / 35.9%. It can be seen that the material obtained in Example 12 is a divalent europium activated zinc barium gallium sulfide green luminescent material.

[0090] Embodiment 13

[0091] The chemical composition synthesized by selecting Example 4 (Series 1) is Eu 0.31 Zn 0.69Ba2Ga6S 12 By packaging the green luminescent material of zinc barium gallium sulfide with a purple LED with an emission wavelength of 400 nm, a green light source LED-1 can be obtained. The electroluminescence spectrum of the LED device is tested using an integrating sphere with a high-precision fast spectroradiometer. It can be found that under different current drives, the luminescent color of the LED-1 device remains stable without obvious deviation.

[0092] Embodiment 14

[0093] The chemical composition synthesized by selecting Example 4 (Series 1) is Eu 0.31 Zn 0.69 Ba2Ga6S 12 The zinc barium gallium sulfide green luminescent material and the commercial red phosphor K2SiF6: Mn 4+ After mixing in a certain proportion and packaging with a blue LED with an emission wavelength of 450 nm, a wide color gamut white LED-2 light source can be obtained, and its color gamut range is >80%NTSC. The electroluminescence spectrum of the LED device is tested using an integrating sphere with a high-precision fast spectroradiometer. It can be found that under different current drives, the luminous color of the white light LED-2 device remains stable without obvious deviation.

[0094] Embodiment 15

[0095] The chemical composition synthesized by selecting Example 4 (Series 1) is Eu 0.31 Zn 0.69 Ba2Ga6S 12 The green luminescent material of zinc barium gallium sulfide and the commercial blue phosphor BaMgAl 10 O 17 :Eu 2+ and commercial red phosphor CaAlSiN3:Eu 2+ After mixing in a certain proportion and packaging with a purple LED with an emission wavelength of 400 nm, a high-quality full-spectrum white LED-3 light source can be obtained, whose typical display index (R1~R8) and special color rendering index (R9~R15) are both greater than 99. The electroluminescence spectrum of the LED device is tested using an integrating sphere with a high-precision fast spectroradiometer. It can be found that under different current drives, the luminous color of the white light LED-3 device remains stable without obvious deviation.

[0096] Table 1 Material emission spectrum data table

[0097]

[0098] Comparative Example 1

[0099] The same chemical composition as described in Example 4 (Series 1) is selected, and the compound chemical formula thereof is: Eu 0.31 Zn 0.69 Ba2Ga6S 12 Eu2O3, ZnS, BaCO3, Ga2O3 and sublimed sulfur powder were used as raw materials. The raw materials were accurately weighed according to the molar ratio of Eu, Zn, Ba, Ga and S of 0.31:0.69:2:6:12. They were sintered at 900°C in a mixed atmosphere of nitrogen (85% by volume) + hydrogen (15% by volume) for 3 h. After cooling, it was found that the nominal chemical composition of Eu could not be obtained. 0.31 Zn 0.69 Ba2Ga6S 12 The XRD test shows that there are a large number of oxide impurities such as Ga2O3 in the material phase, resulting in the material's comprehensive luminescence performance being significantly weaker than the luminescent material prepared in any of the above embodiments. Therefore, the lack of excessive addition of S precursor in the raw material mixture and the sulfur-free atmosphere during the sintering process will have a significant impact on the purity and comprehensive luminescence performance of the material, making the prepared material unable to be applied to the field of LED lighting and display.

[0100] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A divalent europium activated zinc barium gallium sulfide green light-emitting material, characterized in that: The chemical formula of the divalent europium activated zinc barium gallium sulfide green light-emitting material is ZnBa2Ga6S 12 : Eu 2+ , where Eu 2+ As doping ions into the crystal lattice.

2. The divalent europium activated zinc barium gallium sulfide green light emitting material according to claim 1, characterized in that: The chemical formula contains two series: Eu x Zn 1-x Ba2Ga6S 12 and Eu y ZBZ 2-y Ga6S 12 , among which, 0.04≤x≤0.47; 0.05≤y≤0.

54.

3. The divalent europium activated zinc barium gallium sulfide green light emitting material according to claim 1, characterized in that: The excitation spectrum of the luminescent material covers an absorption band of 280~480 nm. Under the excitation of ultraviolet light / violet light / blue light, the main emission peak range of the luminescent material is between 505~530 nm, which is located in the green region; under the excitation of near-ultraviolet / violet light (340~420nm), the best luminescence internal / external quantum efficiency of the luminescent material is not less than 75% / 55%; under the excitation of blue light (420~460 nm), the best luminescence internal / external quantum efficiency is not less than 55% / 35%.

4. The method for preparing the divalent europium activated zinc barium gallium sulfide green light-emitting material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Mixing a Eu precursor, a Zn precursor, a Ba precursor, a Ga precursor and a S precursor to obtain a mixture; the precursor is an oxide, a sulfide, a carbonate or a single substance; (2) The mixture is subjected to a high-temperature solid-phase reaction in a reducing atmosphere containing sulfur vapor to obtain the divalent europium-activated zinc barium gallium sulfide green light-emitting material.

5. The method for preparing the divalent europium activated zinc barium gallium sulfide green light-emitting material according to claim 4, characterized in that: In step (1), in Eu x Zn 1-x Ba2Ga6S 12 In the series, the molar ratio of Eu, Zn, Ba, Ga and S in the precursor is x: (1-x): 2: 6: 19.2, and the amount of S precursor added is 1.6 times the stoichiometric ratio; y ZBZ 2-y Ga6S 12 In the series, the molar ratio of Eu, Zn, Ba, Ga and S in the precursor is y:1:(2-y):6:19.2, and the added amount of S precursor is 1.6 times the stoichiometric ratio.

6. The method for preparing the divalent europium activated zinc barium gallium sulfide green light-emitting material according to claim 4, characterized in that: In step (1), the Eu precursor is selected from one or more of Eu oxides, Eu sulfides or Eu nitrates; the Zn precursor is selected from one or more of Zn oxides, Zn sulfides or Zn nitrates; the Ba precursor is selected from one or more of Ba carbonates, Ba oxides, Ba sulfides or Ba nitrates; the Ga precursor is selected from one or more of Ga oxides or Ga sulfides; the S precursor is selected from sublimated sulfur powder or precipitated sulfur powder.

7. The method for preparing the divalent europium activated zinc barium gallium sulfide green light-emitting material according to claim 4, characterized in that: In step (2), the temperature of the high temperature solid phase reaction is 800-1000°C, and the time of the high temperature solid phase reaction is 2-6 h.

8. The method for preparing the divalent europium activated zinc barium gallium sulfide green light-emitting material according to claim 4, characterized in that: In step (2), the reducing atmosphere of the high-temperature solid phase reaction is hydrogen sulfide gas or a nitrogen-hydrogen mixture containing sulfur vapor, in which the volume content of hydrogen is 10-25%, and the volume content of sulfur vapor is 5-10%; the gas flow rate during the whole preparation process is not less than 200 ml / min.

9. Use of the divalent europium activated zinc barium gallium sulfide green light-emitting material according to any one of claims 1 to 3 or the material prepared by the method according to any one of claims 4 to 8 in display and lighting devices, characterized in that: The lighting device uses the material as a luminescent conversion substance, the luminescent conversion substance is excited by a near-ultraviolet / violet / blue light LED to emit green light, and the display and lighting device uses a near-ultraviolet / violet / blue light LED with a main emission wavelength peak at 365-460 nm as an excitation source.

10. The use according to claim 9, characterized in that: The display and lighting device is a white light LED device, and its color gamut is not less than 80% NTSC.

Citation Information

Patent Citations

  • High efficiency alkaline earth metal thiogallate-based phosphors

    CN101248155A

  • Silicate green fluorescent powder and preparation method thereof

    CN102408890A

  • Rare-earth-doped thiogallate fluorescent powder material and preparation method

    CN105219381A

  • Lutetium aluminate green fluorescent powder and preparation method and application thereof

    CN106590657A

  • Ultraviolet-blue ray excitated aluminate-base narrow-band green fluorescent powder and preparation method thereof

    CN108949168A